2012
DOI: 10.1126/scisignal.2002334
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Modulate Neural Network Activity by Ca 2+ -Dependent Uptake of Extracellular K +

Abstract: Astrocytes are electrically nonexcitable cells that display increases in cytosolic calcium ion (Ca2+) in response to various neurotransmitters and neuromodulators. However, the physiological role of astrocytic Ca2+ signaling remains controversial. We show here that astrocytic Ca2+ signaling ex vivo and in vivo stimulated the Na+,K+-ATPase (Na+- and K+-dependent adenosine triphosphatase), leading to a transient decrease in the extracellular potassium ion (K+) concentration. This in turn led to neuronal hyperpol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
254
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(268 citation statements)
references
References 72 publications
13
254
1
Order By: Relevance
“…In all, although a reduction in extracellular K + results in membrane hyperpolarization at up states and depolarization at down states, the net effect is a stabilization and prolongation of up state combined with depolarization and destabilization of down state. (14). We speculate that a similar mechanism exists in cerebellum and that the transient reduction of extracellular K + hyperpolarized Purkinje cells, which paradoxically prolonged up states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, although a reduction in extracellular K + results in membrane hyperpolarization at up states and depolarization at down states, the net effect is a stabilization and prolongation of up state combined with depolarization and destabilization of down state. (14). We speculate that a similar mechanism exists in cerebellum and that the transient reduction of extracellular K + hyperpolarized Purkinje cells, which paradoxically prolonged up states.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies have shown that astrocytes in hippocampus and cortex increase K + uptake in response to agonist-induced Ca 2+ signaling (14). Fig.…”
mentioning
confidence: 99%
“…[55][56][57][58][59][60]). Astrocytes can also influence neuronal function and synaptic plasticity through active control of extracellular ion concentrations, re-uptake of neurotransmitters from the synaptic cleft and release of gliotransmitters ( [56,[61][62][63][64], but see also [65,66]). This notion of a synapse containing not only pre-and postsynaptic elements but also astrocytic elements is referred to as the 'tripartite synapse' [67][68][69].…”
Section: Intercellular Pathwaysmentioning
confidence: 99%
“…Astrocytes are located adjacent to neurons and are involved in a broad range of functions including synaptic plasticity, neuronal excitability and regulation of the strength of synaptic transmission through the release of glutamic acid, D-serine and adenosine triphosphate [4][5][6][7][8][9]. An elevation in astrocytic calcium concentration has been reported to actively reduce concentration of extracellular potassium ions, which has an impact on neuronal activity [10,11]. The fact that neurons and astrocytes respond synchronously to sensory stimuli, for example stimulation of whiskers in the barrel cortex of mice, also implicates astrocytes in the processing of sensory information [12].…”
Section: Introductionmentioning
confidence: 99%